Detection of abemaciclib, an anti-breast cancer agent, using a new electrochemical DNA biosensor - Lei, Zimeng; Alwan, Merim; Alamir, Hassan Thoulfikar A.; Alkaaby, Hussein Humedy Chlib; Farhan, Sinan Subhi; Awadh, Sura A.; Altimari, Usama S.; Al-Baghdady, Hawra’a Fadhel Abbas; Kadhim, Athmar Ali; Qasim, Maytham T.; Adhab, Ali Hussein; Nekuei, Abuzar (Frontiers in Chemistry, 2022)
Detection of DNA molecules and possible chemotherapy-induced changes in its structure has been the goal of researchers using rapid, sensitive and inexpensive approaches. Therefore, the aim of this study was to fabricate a new electrochemical DNA biosensor using pencil graphite electrodes modified with polypyrrole/Ce doped hexagonal nickel oxide nanodisks or PP/Ce-doped H-NiO-ND composites for determination of Abemaciclib (AMC) and ds-DNA molecules. The DNA biosensor was prepared by immobilizing ds-DNA on the surface of PP/Ce-doped H-NiO-ND/PGE. Differential pulse voltammetry (DPV) was used to electrochemically detect AMC. The results elucidate the extremely high sensitivity of the ds-DNA/PP/Ce-doped H-NiO-ND/PGE biosensor to AMC, with a narrow detection limit of 2.7 nM and a lengthy linear range of 0.01–600.0 μM. The admirable performance of as-fabricated biosensor could be related to the active reaction sites and the unique electrochemical response related to the nanocomposites by enhancing ds-DNA stabilization and accelerating electron transfer on the surface of electrode.